Hypostomus (Siluriformes: Loricariidae) da bacia do rio Ivaí, Paraná, Brasil: descrição de uma nova espécie e redescrição de Hypostomus hermanni (Ihering, 1905) - Dias, Angelica Corrêa (2015)
Hypostomus is one of the most complex and diverse genus of the Loricariidae also the second largest genus of Siluriformes, comprising around 130 valid species, with several being described every year. The distribution of Hypostomus is practically the same as Loricariidae from the La Plata river, Argentina, to Southern of Costa Rica, and widespread in all Brazilian watersheds. In the Ivaí river basin, specimens of that genus were caught and, following current methodologies, were considered to be a new species, which is described herein. Hypostomus sp. N is diagnosed from congeners by having an unusual pattern of pigmentation without, which no spots on body and fins, commonly found in specimens of this genus. In addition, we present here the redescription of Hypostomus hermanni, another congener described from the Tiete River basin, São Paulo State, which is widely distributed in the Paraná State, and Southern of São Paulo State, and still had morphologic limit poorly defined. Finally, we also present a list of species of Hypostomus from the Ivaí River basin, and an identification key for those. Comments about the geographical distribution of these species and congeners are also provided